Comparison of Routine Physiotherapy with and without Thoracic Mobility Exercises in patients with Chronic Neck Pain - Hafiza Mubashra, Moeen Akhtar, Khizra Asif, Hafiza Mubeen Sahar, Muhammad Ashraf, Waqas Latif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cervical pain is a perception anywhere in the posterior region of the cervical spine. Aim: To compare the effectiveness of routine physical therapy with and without thoracic mobility exercises in the treatment of chronic neck pain patients. Study Design: Randomized control trail. Methodology: Total of 81 participants having chronic neck were selected with age ranging from 25 to 53 years. NDI and VAS Performa’s were filled according to study protocol. Patients were divided into two groups A (n=41) and B (n=40) and after every four session’s, questionnaires’ were filled and total 12 sessions will be given to each patients. NDI scale and VAS were used as data collection tool. Analysis of data was done by SPSS v.26. Shapiro-Wilk test was applied. Results: Group A consist of n=41, 50.62% of total data and Group B consist of n=40, 49.38% of data as well. In Group-A, minimum age was observed 25 years and 55 years was the maximum age that accounted similarly 20 years was the minimum age of group-B and 52 years was the highest age. Conclusion: It was concluded that people with interminable neck desolation who got the mix of upper thoracic spine preparation and versatility exercise showed better in general transient results as far as the VSA, NDIKey words: Chronic Neck Pain, VSA,NDI and Thoracic Spine Mobility.